Preferences of permanent training of sports facilities managers in Antioquia, Colombia (Impetus, 2020)
The present study was interested in identifying lifelong learning modalities that would provide routes for the development of labor competencies in managers of sports facilities. Methodologically, a cross-sectional quantitative case study was used. He used the survey as a technique, 185 questionnaires were collected, managers and users of sports facilities participated in the Antioquia Region in Colombia. Their interest in virtual, blended and face-to-face training stands out, being the modality of mixed formation, the one of greater predilection and evidenced a notable lack of training in labor competencies, citizen training and social responsibility in their induction process. The prospective routes of this study are oriented towards the creation of mixed courses that form a model of competencies for the qualification of the labor role of the managers of sports facilities in the aforementioned Region.
Keywords: disciplinary training; management of sports; permanent training; sports facilities; sports manager